The education in values on professionals´ formation from a cuban perspective - Bárbara del C. Roba Lazo; Javier Alejandro Quintero Roba (Universidad de Pinar del Río "Hermanos Saíz Montes de Oca", 2014)
The education in values has been a topic broadly approached in the last decades by authors of different latitudes. In the social development, this constitutes a great problem in the formation of the individuals to who, the social relationships allow them to value, to transform the reality and to be educated, what leads to the formation of the personality. The Cuban universities, as entities open to the society, win more and more partisans in the conception that their purpose is not only to transmit knowledge in its closed environment, but on the contrary, they represent a main socialized agent of education in values aware of the social mission that has given to it by the society that is built, like a formative institution able to solve the necessities of the society. For that reason, it is demanded the integral formation of the professionals. In the work it is approached the education in values from the perspective o the current Cuban society necessities that demands the development of a humanist pedagogy sustained in axiological bases that defend a new pedagogic ethics. It is carried out an analysis of the socialized agencies and the agents in charge of this process, as well as the historical antecedents of the education in values from the Cuban point of view in the different contexts the topic has been studied, as well as the contributions from the Cuban pedagogy to the development of it, indispensable from the integral formation of the Physical Culture professionals.